NATURAL CHARACTERISTICS OF EXPRESSING SIGN AFFIXES -cha/larcha/chasiga, -an, -ona - Asadov , Tulkin Hamroyevich (Innovative Development in Educational Activities, 2023)
The article explores invariable words with independent meanings, i.e. adverbs, specifically, their etymological structure. The morphological, semantic nature of words formed as an adverb is also highlighted. The possibilities of the affixes -ча/-ларча/часига, -ан,-она in word formation, the nature of the words associated with these affixes, the features of each affix in language and speech are thoroughly studied and classified. Subsequent research has provided detailed information on the affixes -ча/-ларча/часига, -ан,-она, word formation possibility of which today are denied, their formation of new words, some usual and occasional constructions related to these affixes are analyzed. Each theoretical view is verified by examples.